2019
DOI: 10.1093/nar/gkz699
|View full text |Cite
|
Sign up to set email alerts
|

EWS–FLI1 modulated alternative splicing of ARID1A reveals novel oncogenic function through the BAF complex

Abstract: Connections between epigenetic reprogramming and transcription or splicing create novel mechanistic networks that can be targeted with tailored therapies. Multiple subunits of the chromatin remodeling BAF complex, including ARID1A, play a role in oncogenesis, either as tumor suppressors or oncogenes. Recent work demonstrated that EWS–FLI1, the oncogenic driver of Ewing sarcoma (ES), plays a role in chromatin regulation through interactions with the BAF complex. However, the specific BAF subunits that interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 50 publications
3
48
1
Order By: Relevance
“…As outlined before, a recent study revealed a direct interaction of EWSR1-FLI1 with the BAF complex via its subunit ARID1A [80]. The authors could show that ARID1A was differentially spliced and accumulated in its long isoform ARID1A-L in the presence of EWSR1-FLI1.…”
Section: Targeting Protein-protein Interactions Of Fusion Oncoproteinsmentioning
confidence: 72%
See 1 more Smart Citation
“…As outlined before, a recent study revealed a direct interaction of EWSR1-FLI1 with the BAF complex via its subunit ARID1A [80]. The authors could show that ARID1A was differentially spliced and accumulated in its long isoform ARID1A-L in the presence of EWSR1-FLI1.…”
Section: Targeting Protein-protein Interactions Of Fusion Oncoproteinsmentioning
confidence: 72%
“…One of the subunits of the chromatin remodeling BAF complex, ARID1A, has been recently shown to be a splicing target of EWSR1-FLI1 [80]. ARID1A-L generated by alternative splicing in EwS cells plays an important role in tumor growth and promotes the stability of EWSR1-FLI1.…”
Section: Targeting the Splicing Machinery Involved In Post-transcriptmentioning
confidence: 99%
“…In this regard, the splicing signature of human cancers is emerging as a powerful tool to distinguish tumor subtypes and stratify patients [32,33]. Notably, although alternative splicing dysregulation has also been reported in Ewing sarcoma [24,[34][35][36][37][38], limited information is available regarding the RBPs responsible for this process and their possible association with prognosis. An important regulator of RNA metabolism with strong implications in Ewing sarcoma malignancy is the DNA/RNA helicase DHX9, which interacts with the oncogene EWS-FLI1 and promotes its transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Like the wild-type FET proteins, EWS-FLI1 binds RNA Pol II, as well as a number of transcription factors and enhancer or repressor complexes [24][25][26][27] . Nevertheless, the mechanism for EWS-FLI1 to broadly modulate transcription remains incomplete.…”
Section: Introductionmentioning
confidence: 99%